Rewriting and Appropriating Francesco Guicciardini’s Storia D’Italia in Elizabethan England: Geoffrey Fenton’s Translation and Shakespeare’s Henry V - Zaharia Oana-Alis (Messages, Sages and Ages, 2016)
The exploration of the multifarious ways in which cultural reworkings and translations have been involved in the transmission and circulation of various discourses, concepts and ideas in different historical periods and places, has become one of the most productive fields of inquiry in Early Modern Studies. Both translation and cultural reworking have been understood as forms of rewriting that involve altering, reinterpreting and adapting texts (Fischlin&Fortier, 2000; Lefevere, 1992). The main difference between the two concepts lies in their relation to the text/texts they are supposed to rewrite. Thus, translations are related to more direct and evident means of appropriation and rewriting, most often acknowledging themselves as attempts to render a specific text from one language/culture into another. Cultural reworkings, on the other hand, presuppose the appropriation and remaking of various texts and discourses in a more indirect manner, without necessarily pointing to the particular texts that are being rewritten. They represent threads that can be identifiable or at times altered beyond recognition, frequently leading to the creation of a completely different text. Therefore, cultural reworking involves the appropriation, rewriting and recontextualization - more or less explicit- of literary and non-literary texts and discourses that belong to the, cultural, political and ideological context of a certain work.